Management of Pediatric and Adolescent Type 2 Diabetes - M. Constantine Samaan (International Journal of Pediatrics)
Type 2 diabetes (T2D) was an adult disease until recently, but the rising rates of obesity around the world have resulted in a younger age at presentation. Children who have T2D have several comorbidities and complications reminiscent of adult diabetes, but these are appearing in teens instead of midlife. In this review, we discuss the clinical presentation and management options for youth with T2D. We discuss the elements of lifestyle intervention programs and allude to pharmacotherapeutic options used in the treatment of T2D youth. We also discuss comorbidities and complications seen in T2D in children and adolescents.